Object-oriented technology and computing systems re-engineering - Zedan, H. S. M.; Cau, A. (Antonio); ScienceDirect eBooks; Colloquium on Object Technology and System Re-engineering (1998 : Oxford University) (Chichester : Horwood, 1999)
This book delivers the latest developments in object technology and their impact in computing systems re-engineering. Object-oriented programming is here shown to provide support for constructing large scale systems that are cheaply built and with reusable components, adaptable to changing requirements and use efficient and cost-effective techniques. Internationally recognised authorities from Finland, France, Germany, Italy, Poland, Spain, the UK and the USA here record their research and development work on the industrial techniques and structured object-oriented methodologies in forward and reverse engineering of computing systems. This book takes stock of progress of that work showing its promise and feasibility, and how its structured technology can overcome the limitations of forward engineering methods used in industry. Forward methods are focused in the domain of reverse engineering to implement a high level of specification for existing software. The book contains the selected, quintessential content of the first UK Colloquium on Object Technology and Systems Re-Engineering held at Oxford University in 1998. The conference was sponsored by British Telecom Laboratories, EMSI limited and the OOSP Specialised Group of The British Computer Society. Delivers the latest developments in object technology and their impact in computing systems re-engineeringProvides support for constructing large scale systems that are cheaply built and with reusable components, adaptable to changing requirements and use efficient and cost-effective techniquesContains the content of the first UK Colloquium on Object Technology and Systems Re-Engineering held at Oxford University in 1998.
7.4 CONCLUSIONS AND FUTURE WORK7.5 REFERENCES; Chapter 8. Agent Oriented Programming Language LASS; 8.1 INTRODUCTION; 8.2 LASS; 8.3 LASS SPECIFICATION OF A PERSONAL DIGITAL ASSISTANT; 8.4 RELATED WORK; 8.5 CONCLUSION; 8.6 REFERENCES; Chapter 9. Fair Objects; 9.1 INTRODUCTION; 9.2 SEMANTIC FRAMEWORK; 9.3 FAIR OBJECTS; 9.4 TELEPHONE FEATURE EXAMPLES; 9.5 CONCLUSION; 9.6 REFERENCES; Chapter 10. Systems of Systems as Communicating Structures; 10.1 INTRODUCTION; 10.2 COMMUNICATING STRUCTURES; 10.3 C++/CSIM CONSTRUCTS; 10.4 THE COMMUNICATING STRUCTURE OBJECTS; 10.5 THE COMMUNICATING PROCESSES.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Elsevier
Keywords: Object-oriented methods (Computer science) -- Congresses; Software reengineering -- Congresses; COMPUTERS -- Software Development & Engineering -- General; Object-oriented methods (Computer science); Software reengineering; Electronic books